Digitalisasi UMKM Inklusif di Kabupaten Banyumas sebagai Katalis Transformasi Sosial Menuju Ekonomi Berkelanjutan - Putri, Puspita Lianti; Salsabela, Riska Nadiya (Seminar Nasional Penelitian dan Pengabdian Kepada Masyarakat 2025, 2025)
This community engagement program aims to foster social and economic transformation through the inclusive digitalization of Micro, Small, and Medium Enterprises (MSMEs) in Banyumas Regency. The program focuses on enhancing digital literacy and online marketing capabilities to enable entrepreneurs to adapt to a technology-driven economy. The implementation methods include a digital needs assessment, two-stage training on digital business management and creative marketing strategies, and four weeks of intensive mentoring using a need-based participatory approach. A total of 30 MSMEs from vulnerable groups and peri-urban areas participated actively in the program. Evaluation results show significant improvements in digital competencies, including an increase in understanding of digitalization concepts from 26% to 88% and the use of WhatsApp Business from 34% to 92%. The novelty of this program lies in the application of a context-based digital mentoring model rooted in local community engagement, integrating digital literacy with the strengthening of socio-economic networks. This inclusive and contextual approach has proven effective as a catalyst for social transformation and as a driver of inclusive and sustainable regional economic growth.